THE ROLE OF QUALITY ASSURANCE STANDARDS IN PRODUCT MARKETING: A PILOT STUDY OF THE OPINIONS OF MANAGERS AND EMPLOYEES AT KARWANCHI SOFT DRINKS AND JUICES COMPANY IN KIRKUK - Salahddin Shibil Jasim Aljubory; Walaa hazem seltun (Scholar Express Journals, 2025)
The current study aims to identify the influence relationships between Quality Assurance Standards (QAS) and product marketing in Karwanchi Soft Drinks and Juices Company in Kirkuk. To achieve this, the research variables were defined, and hypotheses were formulated. The researcher used a questionnaire as the primary data collection tool, supplemented by various statistical methods to test the hypotheses.
Keywords: Quality assurance standards; product marketing; continuous improvement